2010
DOI: 10.1159/000320270
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Bilateral Cochlear Implantation in Children: Development of the Primary Auditory Abilities of Bilateral Stimulation

Abstract: The advantages of sequential bilateral cochlear implantation were assessed in 29 children with a severe to profound hearing loss. The effect of age at second implantation and the effect of duration of bilateral implant use on the outcomes in speech perception and directional hearing were investigated. The children received their second cochlear implant at an age ranging from 2.8 to 8.5 years. Measurements were carried out preoperatively and postoperatively after 6, 12 and 24 months of bilateral implant use. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
61
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 40 publications
(57 reference statements)
11
61
3
2
Order By: Relevance
“…Bilateral performance was significantly better than either ear alone at the 18-month and 3-year test intervals for children receiving CI2 before 8 years of age and by the 2-year test interval for children receiving CI2 after 8 years of age. In contrast, Sparreboom et al (2011) identified an early bilateral advantage at the 6-month test interval that was no longer present at the 12-and 24-month intervals.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…Bilateral performance was significantly better than either ear alone at the 18-month and 3-year test intervals for children receiving CI2 before 8 years of age and by the 2-year test interval for children receiving CI2 after 8 years of age. In contrast, Sparreboom et al (2011) identified an early bilateral advantage at the 6-month test interval that was no longer present at the 12-and 24-month intervals.…”
mentioning
confidence: 69%
“…Studies of children receiving CI2 at a younger age have reported bilateral lateralization or localization benefit. Sparreboom et al (2011) reported significant bilateral improvement at the 24-month postbilateral interval. Sound localization improved significantly for 74%-83% of participants across visits in Asp et al (2015) and sound localization was significantly related to age at CI2.…”
Section: Localizationmentioning
confidence: 94%
See 3 more Smart Citations